Moving Beyond Evaluation to Transit Project Prioritization: Lessons from the Toronto, Ontario, Canada, Context. Issue 1 (2016) - Nagorsky, Becca; Sabag, Kaya; Emerson, Don; Hewitt, Stephen
Governments face critical decisions on how to spend taxpayers' money and must weigh priorities and come to these decisions in a transparent and defensible way. A prioritization tool can play a critical role in informing spending decisions, ensuring that decisions are made in the interest of the public good, and bolstering public confidence in elected officials and the democratic process. Ideally, a prioritization tool not only evaluates potential projects against a desired set of policy objectives but also prioritizes potential projects into an implementation plan through the integration of pragmatic considerations. Metrolinx, an Ontario, Canada, provincial agency tasked with transportation planning for the greater Toronto and Hamilton area, developed a prioritization framework to make recommendations on capital investment in sustainable transportation. This paper summarizes the current prioritization framework, outlines its limitations, and goes on to explore potential remedies to those limitations as well as inherent challenges. Specifically, the paper discusses incorporating broader considerations, including multimodal integration and active transportation, congestion, network effects, and project interdependencies, and bridging the gap between project evaluation and real-world prioritization. The paper presents best-practice research for each broader consideration and posits that these broader considerations can be used to transform evaluation outputs into prioritized implementation plans.